EFFECT OF ION PAIRS ON DECREASE THE RISK OF USING SALINE WATER FOR IRRIGATION - & Esmail, Rajab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This investigation was conducted during January, 2018 to April, 2019 to investigate the role of correcting ion pairs and activity in decreasing the risk of saline water for irrigation. The groundwater of (31) wells in Makhmur district were depended in this study .The results indicated that amount of ions contributing in ion pairing was ranged between (0.77 -15.42 mmole l-1) with the mean of 6.56 mmole l-1.and the dominate ion pairs were (CaSO4)0, (MgSO4)0,(MgHCO3)+ and (CaHCO3)+,with the values of 5.00, 4.50, 2.37 and 1.33 mmolc l-1 respectively. The studied saline  water in Makhmur  district did not suitable for irrigation the soils having low, medium and high permeability, while after correcting ion pairs and activity 14 of the studied saline waters were suitable for irrigation (3 of them for soil having medium permeability and 11 of them for soils having high permeability). It means correcting ion pairs and activity caused removal the risk of 14 saline waters for irrigation or caused decrease the risk of 45% of the studied saline water. Correcting ion pairs and activity caused shifting water class from no suitable for irrigation to suitable for irrigation depending on salinity potential values and Doneen classification.